KEMAMPUAN SANTRI BARU BERADAPTASI DALAM MASA PANDEMI COVID-19 DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - abdi fauji (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The ability of children to adapt to the Covid-19 Pandemic Period at Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi as a conscious effort designed for personality in adaptation in Islamic boarding schools. There are several abilities of children that adapt quickly, some have long adaptations according to their respective personalities. Problems that weaken the students are children who often cry, are quiet, do not want to hang out, like to be alone and so on. This study used a qualitative approach. This type of research was descriptive in order to understand the main components of children's ability to adapt in the Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi. Data collection is carried out in research through 1) observation 2) interviews 3) documentation. The findings that can be presented are, 1) the forms of adaptation in the Pondok Pesantren Darussalam Blokagung Tegalsari with two aspects, namely adaptive through indicators; a) physical changes, b) changes in social behavior, and 3) social attractiveness, while the second aspect is through indicators: a) intention, b) values, and c) empathy. 2) factors in adapting to the Darussalam Blokagung Tegalsari Islamic Boarding School, Banyuwangi include: 1) External factors a) family environment, 2) school environment and 2) internal factors, a) physical condition, 2) personality, and 3) learning process .